EFFECTIVE COMMUNICATION FOR TOURISM IN TSUNAMI MUSEUM BANDA ACEH: DEVELOPING SPEAKING SKILLS THROUGH COLLABORATION. - RISKA NAHARA SAPUTRI; DENTIANA DENTIANA; FATIN NADIFA BR TARIGAN (LINGUISTICA, 2023)
Tourism is a rapidly growing industry globally and is currently a source of employment and livelihood for many people. Tourism development in the region as one of the development sectors cannot be separated from the development of local communities and the construction of supporting facilities. One of the success factors in the development of a tourist destination is communication. Through communication, opportunities for the fame of a tourist destination will open up to be widely known by the wider community. This study aims to describe tourism communication and develop speaking skills through collaboration in Banda Aceh. This study uses qualitative research. This type of approach in qualitative research is a case study approach. Case study is a method that exploits a bound contemporary system (a case) as well as several bound contemporary systems (multi cases) in the real world all the time, through detailed data collection. The application of communication by the manager of the Tsunami Museum tourist attraction in Aceh is on the theory of communication effectiveness which includes cognitive, affective, and behavioral aspects.